Board Diversity and Corporate Social Responsibility Disclosure in ASEAN Banking Industry - Reysvana Rukmana Cakti; Doddy Setiawan; Y Anni Aryani (Accounting Analysis Journal, 2022)
Purpose : First, to find the determining factors which affects CSR disclosure in the ASEAN banking industry by examining the effect of diversity from gender, board size, and education. Second, observe and analyze the level and variation of ASEAN banking CSR disclosures.Method : This study uses a sample of the ASEAN banking industry with an observation period of 2017-2019. The bank annual report was examined to analyze the bank CSR disclosures using content analysis and panel data analysis.Findings : The inclusive results of this study reveal that there is a positive and significant effect of board education diversity on CSR disclosure of bank. Meanwhile, the diversity for board size and board gender is not significant for bank CSR disclosure. Based on statistical calculations, the level of CSR disclosure of banks varies from 13.09 percent to 27.89 percent, with on average they report each is Thailand 27.89 percent, Philippines 13.09 percent, Malaysia 17.04 percent, Singapore 14.49 percent, and Indonesia 25.17 percent.Novelty : First, this study contributes to the CSR literature, because the banking industry is generally avoided from CSR studies. Second, this study offers empirical evidence of board diversity on CSR disclosure. Third, adopts a cross-country approach across ASEAN rather than just one country. Fourth, present the results of the analysis under the CSR disclosure indicators GRI-G4 : financial service. Keywords : Corporate Social Responsibility Disclosure; Board Diversity; ASEAN; Banking Industry